Enhancing adaptability in educational research: the role of AI-Driven Tools in VUCA environments - Dewi, Desi Surlitasari; Siahaan, Safnidar; Wilany, Eka; Adam, Adam; Ramadhani, Riska; Saicindo, Shita Aulia; Ardhi, Mega Aulia (Panicgogy International Journal, 2025)
This study explored how Artificial Intelligence (AI) tools enhanced the adaptability of research methodologies in the field of education, particularly in environments characterized by volatility, uncertainty, complexity, and ambiguity (VUCA). With the rapid pace of change in educational settings, AI technologies such as automated data analysis, intelligent learning systems, and natural language processing (NLP) were increasingly used by educational researchers. This research focused on identifying how AI-driven tools helped educational researchers respond flexibly and effectively to challenges that arose in complex and uncertain contexts. The researchers recommended developing comprehensive training programs for educators to enhance AI literacy, establishing ethical guidelines for AI in education focusing on data privacy, algorithmic fairness, and transparency, and encouraging interdisciplinary collaboration among educators, technologists, and policymakers to create scalable, equitable, and sustainable AI-enhanced learning frameworks, ensuring that AI's potential was harnessed for the benefit of all learners.